2011
DOI: 10.1007/s10661-011-2019-5
|View full text |Cite
|
Sign up to set email alerts
|

Distributions and sources of polycyclic aromatic hydrocarbons in surface sediments from the Cross River estuary, S.E. Niger Delta, Nigeria

Abstract: Polycyclic aromatic hydrocarbon (PAH) analyses of surface sediments from the Cross River estuary by gas chromatography-mass spectrometry indicated natural diagenetically derived PAHs in the upper estuary, with minor and variable amounts of petrogenic and combustion-derived PAHs from human activities (lower estuary). The occurrence of significant amounts of perylene (average 23% of all PAHs) with the diagenetic natural PAHs in the middle estuary bordered by mangrove forests supports its origin from terrestrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…In these solvent blanks, we report low molecular weight PAHs as both parent [e.g., naphthalene (N), anthracene (A) and phenanthrene (P)] and their alkyl homologs dimethylphenanthrenes (DMP), and trimethylphenanthrenes (TMP)] as shown in the mass chromatograms (Figure 2a and b). These patterns are similar to those reported for some sediment samples from the Cross River Estuary, especially those collected near its mouth (Oyo-Ita, 2007) and have been deleted from a subsequent report for the same samples (Ekpo, et al, 2011). In the case of these solvents, the origin of the PAH contaminants is likely from carry over in the production of the hexane and petroleum ether by simple distillation of petroleum products yielding only a technical grade purity (typically 70%).…”
Section: Polycyclic Aromatic Hydrocarbonssupporting
confidence: 76%
“…In these solvent blanks, we report low molecular weight PAHs as both parent [e.g., naphthalene (N), anthracene (A) and phenanthrene (P)] and their alkyl homologs dimethylphenanthrenes (DMP), and trimethylphenanthrenes (TMP)] as shown in the mass chromatograms (Figure 2a and b). These patterns are similar to those reported for some sediment samples from the Cross River Estuary, especially those collected near its mouth (Oyo-Ita, 2007) and have been deleted from a subsequent report for the same samples (Ekpo, et al, 2011). In the case of these solvents, the origin of the PAH contaminants is likely from carry over in the production of the hexane and petroleum ether by simple distillation of petroleum products yielding only a technical grade purity (typically 70%).…”
Section: Polycyclic Aromatic Hydrocarbonssupporting
confidence: 76%
“…Although Phe may be the result of background occurrence such as biogenic sources (Wilcke, 2007;Cabrerizo et al, 2011), the results showed that the Phe/An ratio was b10 at most sites (mean 0.73), suggesting pyrogenic sources such as emissions from combustion of gasoline (Lima et al, 2005). Furthermore, Fl/(Fl + Pyr) ratios differentiate petroleum input from combustion processes (Yunker et al, 2002;Ekpo et al, 2012). For Fl/(Fl + Pyr), low ratios (b 0.40) indicate petroleum, intermediate ratios (0.40-0.50) liquid fossil fuel combustion, whereas ratios N0.50 are characteristic of grass, wood, or coal combustion.…”
Section: Source Identificationmentioning
confidence: 93%
“…between 0.40 and 0.50 indicating liquid fossil fuel combustion such as vehicular exhaust emission. Ratios over 0.50 are attributed to grass, wood, or coal combustion(Yunker et al 2002;Christensen and Bzdusek 2005;Ekpo et al 2011). In our study, Fla/ (Fla + Pyr) ratios for the termite nest wall, soil, and sediment samples were in the range 0.40-0.50(Table 1)indicating liquid fossil fuel combustion input.…”
mentioning
confidence: 49%